Tourism development strategy in South Central Timor (TTS) regency, East Nusa Tenggara Province (NTT), Indonesia - Yosefina Dhae; Markus Bunga; Wehelmina Ndoen; Christien Foenay; Anderias Anabuni (Cita Konsultindo Research Center, 2023)
Tourism is one of a major sector in many countries to develop its economy. This research aims to analyze the local government strategy to develop tourism. This research was conducted with a qualitative approach with case study method, using in-depth interviews, observations, and documentation as data collection tools. Then, data was analyzed using the Milles and Huberman model which consisted of three activity namely: data reduction, data presentation, and drawing conclusions. This research found that the TTS Regency government strategy to develop tourism are applying tourism village program, empowering the community through training activities, business assistance, financial assistance, and also by providing infrastructure. However, this has not been done optimally by the government due to the small portion of tourism budget and the absence of investors and unresolved land ownership problems. Therefore, the government must solve problems with the community related to land ownership, provide adequate funding sources to support the tourism sector by inviting both domestic and foreign investors and/or private sector tourism operators.